An expert system to design composting facilities for municipal solid waste - Noor Ezlin Ahmad Basri,; Hassan Basri,; E.I. Stentifor, (2005)
An expert system prototype, Compost Design Consultant (CDC), was developed to aid the preliminary design of composting facilities for municipal solid waste. The prototype development process for the CDC adopted a modular approach, which covered the main design tasks for the selected composting system. These covered,' the reception facilities, the materials handling equipment, the storage facilities, pretreatment processes, feedstock conditioning, composting process control, posttreatment processes, site requ,irements, operational considerations, market planning and environmental considerations. An expert system shell, Kappa-pc (version 2.1), was preferred as the building tool for the development of the prototype because of its object-oriented approach that combines the two main knowledge representation techniques, i.e. production rules and objects. It was also found to offer advantages with respect to ease of manipulation, increased productivity and a true windowing capability to run on personal computers. The main issues addressed in the expert system development were the knowledge acquisition process and the building of the prototype. The major steps involved were problem definition, implementation and testing. The knowledge used in the system was acquired from many sources such as textbooks, manuals and guidelines, journals, reports, case studies and domain experts. In the CDC consultation process, the user can evaluate the most suitable composting system for a particular site based on local conditions, and other design requirements for the facility. A summary of the system's recommendations and additional information on the Composting System Module was shown as an example to evaluate the performance of CDC consultation process, which was considered satisfactory. The primary , end-users of the CDC would be consulting engineers, waste management engineers, recycling coordinators, municipal managers and decisions-makers, who would use it as an aid to their decision making process